Ammiralius, Mirdalim, Amirdalis – the creation of Muslim commanders during the struggle of Antioch in the First Crusades’ sources (until about the mid-twelfth century) - Pełech, Tomasz (In Gremium. Studies in History, Culture and Politics, 2020)
The article considers three main issues. Firstly, it concerns the representation of secondary Muslim commanders in the accounts created by the participants of the expedition to Jerusalem (Gesta Francorum, Historia de Hierosolymitano Itinere, Historia Francorum and Historia Hierosolymitana), in the descriptions of the military struggles under the city of Antioch between the Crusaders and atabeg of Mosul, Kurbugha. Secondly, it deals with the issue of the transmission of content in the sources of the next generations of the First Crusade’s historians (until around the mid-twelfth century). Thirdly, it is an attempt to identify people known from Latin and Arabic sources with real historical figures.